Results of diagnosing the level of innovative competence for secondary school teachers - Нижник, О. С. (Scientific notes of the pedagogical department, 2020)
One of the higher-priority directions concerning improvement of the institution of general secondary education is the adaptation of teachers’ educational, scientific methodological and organizational activities to the modern challenges. The orientation of the new Ukrainian school to the world educational standards calls for new approaches to the organization of the educational process in institutions of general secondary education, the formation of up-to-date eﬀective innovative competence of teacher-practitioners. In order to diagnose the level of formation of teachers’ innovative competence a summative experiment was conducted as a method to obtain and fix theoretical and empirical data. In the course   of the research the criteria for innovative competence evaluation were developed, diagnostic tools were selected, diagnostic procedures and the analysis of the obtained results were conducted. A methodological workshop was held for teachers aimed at defining such basic concepts as «innovative pedagogical activity», «competence», «innovative competence» The level of the formation of teachers’ innovative competence was diagnosed taking into account its components, namely: operational (the formation of intellectual abilities, the quickness of mental operations, ability to solve problem situations), professionalvalue (motivation to obtain innovative competences, professional orientation, ability to self-control and urge for constant professional self- improvement, formation of individual style of pedagogical activity, professionally important personal qualities). Having generalized the results of applying various diagnostic methods (the technique «Six Thinking Hats» by Edward de Bono, the technique of studying the value scales by M.  Rokeach, the diagnostic test «Readiness for self-development», «Strategies to form a higher level of basic need for cognition» by Palchevsky, «The methodology of limit meanings» by D. Leontiev) the level of formation of innovative competence of the teacher of the institution of general secondary education was determined.